Utilidad de los índices plaquetarios en el diagnóstico diferencial de enfermedades que cursan con alteraciones en las plaquetas (2010)
ABSTRACT: The use of platelet indices as a diagnostic tool has become very relevant in the use of hematological and non-hematological entities. Recent advances in technology have made possible to use these parameters in the differential diagnosis, in the patient’s prognosis and monitoring in diseases with platelet alterations (in amount or morphology). The Mean Platelet Volume (MPV) and the Platelet Distribution Width (PDW), according to the platelets size the MPV and the PDW made posible to discriminate if the thrombocytopenia is caused by a bone marrow production’s defect or an intrinsic damage, using those indices as a positive or negative predictive value in neoplasic process. Also, immune platelet is used to evaluate severe thrombocytopenias (less than 20 x 103/μL), as the ones presented in the patient’s treatment after the chemotherapeutic process. As it happens in the myeloproliferative syndromes, the increase of P-LCR (for platelet higher than 12 fL), PMV and PDW supports the platelet’s morphologic changes, as the presence and activity of young platelets is determined by the reticulated platelet, while the reticulated platelet index (IPR) indicates marrow response and if a transfusion is needed.